Catalytic Atroposelective C7 Functionalisation of Indolines and Indoles. Issue 1 (5th November 2021) - Shaaban, Saad; Merten, Christian; Waldmann, Herbert
Abstract: Axially chiral atropisomeric compounds are widely applied in asymmetric catalysis and medicinal chemistry. In particular, axially chiral indole‐ and indoline‐based frameworks have been recognised as important heterobiaryl classes because they are the core units of bioactive natural alkaloids, chiral ligands and bioactive compounds. Among them, the synthesis of C7‐substituted indole biaryls and the analogous indoline derivatives is particularly challenging, and methods for their efficient synthesis are in high demand. Transition‐metal catalysis is considered one of the most efficient methods to construct atropisomers. Here, we report the enantioselective synthesis of C7‐indolino‐ and C7‐indolo biaryl atropisomers by means of C−H functionalisation catalysed by chiral Rh Jas Cp complexes. Abstract : The first enantioselective synthesis of C7‐indolino‐ and C7‐indolo‐biaryl atropisomers by means of C−H functionalisation catalysed by our chiral rhodium complex (Rh Jas Cp) is reported. The reaction works for a wide range of substrates and gives excellent yields (up to 92 %) and very good level of enantioselectivity (up to 90 % ee ). Furthermore, this transformation tolerates a variety of functional groups in both indoles and indolines.